Association of Retinal Artery Occlusion with Subclinical Coronary Artery Disease - Kim, Yong Dae; Kim, Yong-Kyu; Yoon, Yeonyee E.; Yoon, Chang-Hwan; Park, Kyu Hyung; Woo, Se Joon (Journal of Korean medical science, 2019)
To evaluate the association between retinal artery occlusion (RAO) and subclinical coronary artery disease (CAD). We studied 41 patients with non-arteritic RAO without any history or symptoms of CAD, who had undergone coronary computed tomographic angiography (CCTA) for systemic atherosclerotic evaluation between 2007 and 2012. The age- and gender-matched control group comprised 4-fold subjects who were randomly selected from asymptomatic subjects who underwent CCTA during general health evaluation. Medical records and CCTA findings were compared between RAO patients and control groups. Multiple logistic regression analysis was carried out to assess the risk factors associated with CAD. Cardiovascular risk factors were not significantly different between RAO patients and control groups. RAO patients showed higher coronary artery calcium score than did control subjects (267.9 ± 674.9 vs. 120.2 ± 289.5). On CCTA, the prevalence of obstructive CAD (diameter stenosis ≥ 50%) in RAO patients was significantly higher than that in controls (29% vs. 15%; odds ratio [OR], 3.0). RAO patients demonstrated a significantly higher segment-involvement score (SIS) (2.6 ± 3.0 vs. 1.6 ± 2.4) and segment-stenosis score (SSS) (3.6 ± 4.8 vs. 2.0 ± 3.3) than did controls. After adjustment of associated factors, RAO showed significant association (OR, 3.0) with obstructive CAD and extensive CAD (SIS > 4: OR, 2.8; SSS > 8: OR, 3.4). Patients with RAO had a higher prevalence of subclinical obstructive CAD with a more extensive and heavier burden of coronary artery plaques than did age- and gender-matched controls. Physicians should understand the potential risk of CAD in RAO patients.